2021
DOI: 10.3389/fmicb.2021.631853
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Methyl Esters From the Coral-Associated Bacterium Pseudomonas aeruginosa Inhibit Virulence and Biofilm Phenotypes in Multidrug Resistant Staphylococcus aureus: An in vitro Approach

Abstract: In an attempt to study the antibacterial, antivirulence and antibiofilm potentials of bacteria residing the tissue and surface mucus layers of the pristine corals, we screened a total of 43 distinct bacterial morphotypes from the coral Favites sp. Among the isolates, Pseudomonas aeruginosa strain CBMGL12 with showed antibacterial, antivirulence and antibiofilm activity against multidrug resistant pathogenic strains of Staphylococcus aureus (reference strain: MTCC96; community-acquired methicillin resistant str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The IR spectra of bacterial biofilm in the presence of CMT + light showed a narrow and weak stretch of functional groups, giving evidence of remarkable change in the carbohydrate and protein composition of the extracellular matrix of S. aureus . A significant alteration was mainly observed in the 1659 cm –1 stretch which mainly accounts for the pathogenesis related protein synthesis . In a recent work, a qualitative study found changes in the stretch of the amide group that are mainly associated with the conformation change in the proteins responsible for the biofilm forming extracellular matrix of S. aureus .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The IR spectra of bacterial biofilm in the presence of CMT + light showed a narrow and weak stretch of functional groups, giving evidence of remarkable change in the carbohydrate and protein composition of the extracellular matrix of S. aureus . A significant alteration was mainly observed in the 1659 cm –1 stretch which mainly accounts for the pathogenesis related protein synthesis . In a recent work, a qualitative study found changes in the stretch of the amide group that are mainly associated with the conformation change in the proteins responsible for the biofilm forming extracellular matrix of S. aureus .…”
Section: Resultsmentioning
confidence: 98%
“…A significant alteration was mainly observed in the 1659 cm −1 stretch which mainly accounts for the pathogenesis related protein synthesis. 38 In a recent work, a qualitative study found changes in the stretch of the amide group that are mainly associated with the conformation change in the proteins responsible for the biofilm forming extracellular matrix of S. aureus. 39 Another study reported the reduction in the functional moieties revealing the effect of Pseudomonas aeruginosa extract on a biofilm of multidrug resistant S. aureus by reduction of the virulence protein responsible for the hemolysins and proteases.…”
Section: Biofilm Assay For Activity Of Curcumin Loadedmentioning
confidence: 99%
See 1 more Smart Citation
“…5B), suggesting microbiome acclimation. While their function remains largely unknown, these taxa have been found in the microbiomes of healthy corals (Chu and Vollmer, 2016; McKew et al, 2012; Vijay et al, 2021) and may provide benefits for A. pulchra when exposed to increased runoff during the wet season given their overrepresentation in the mucus (Fig. 7A).…”
Section: Discussionmentioning
confidence: 99%
“…5B & C) with mucus mirobiomes dominated by Comamonadaceae, Moraxellaceae, Chitinophagaceae, and Pseudomonadaceae. Pseudomonadaceae have previously been described from the mucus of healthy corals and are known for their antibacterial, antiviral, and antifouling properties that allow for control of viruses and prevention of biofilm formation (Vijay et al, 2021), linking this taxon to potential roles in microbiome regulation. Moraxellaceae, such as Psychrobacter spp., have also been described from coral mucus samples (McKew et al, 2012) and possess genes associated with carbon and nitrogen metabolism that may confer the ability to utilize organic compounds found in the mucus (Badhai, Ghosh and Das, 2016).…”
Section: Discussionmentioning
confidence: 99%